Guselkumab in the treatment of patients with plaque psoriasis of moderate and severe severity: Efficacy and safety of interleukin-23 blockade - V. V. Chikin (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Materials and methods. In this paper, we review publications on the significance of interleukin-(IL)-23 in the pathogenesis of plaque psoriasis and analyse the results of the 1st and 2nd phase clinical studies, as well as the 3rd phase comparative studies VOYAGE 1, VOYAGE 2, NAVIGATE and ECLIPSE on the efficacy and safety of Guselkumab - a blocker of the p19 subunit in IL-23. The review was conducted using the scientific literature databases PubMed and RSCI.Results. The high efficiency and safety of Guselkumab in the treatment of patients with plaque psoriasis is demonstrated. The PASI 90 value during Guselkumab treatment reached 73.3 % and 80.2 % at the 24th and 16th week (VOYAGE 1). The therapeutic effect persisted following treatment for 48 weeks. It is shown that Guselkumab therapy is effective in patients having undergone unsuccessful therapy with other genetically engineered biological preparations. The reviewed comparative studies show a higher  therapeutic efficacy of Guselkumab compared to TNF-α blockers, IL-12/23 p40 subunit, IL-17. The incidence of adverse events during therapy using Guselkumab and other biological drugs used in comparative studieswas low and comparable.Conclusion. The IL-23 subunit p19 blocker Guselkumab is an effective and safe drug for the treatment of patients with plaque psoriasis of moderate and severe severity.